Radiosynthesis and First-In-Human PET/MRI Evaluation with Clinical-Grade [18F]FTC-146 - Shen, Bin; Park, Jun Hyung; Hjørnevik, Trine; Cipriano, Peter W.; Yoon, Daehyun; Gulaka, Praveen K.; Holly, Dawn; Behera, Deepak; Avery, Bonnie A.; Gambhir, Sanjiv S.; McCurdy, Christopher R.; Biswal, Sandip; et al. (Molecular imaging and biology, 2017)
Purpose Sigma-1 receptors (S1Rs) play an important role in many neurological disorders. Simultaneous positron emission tomography (PET)/magnetic resonance imaging (MRI) with S1R radioligands may provide valuable information for diagnosing and guiding treatment for these diseases. Our previously reported S1R radioligand, [ 18 F]FTC-146, demonstrated high affinity for the S1R ( K i = 0.0025 nM) and excellent selectivity for the S1R over the sigma-2 receptor (S2Rs; K i = 364 nM) across several species (from mouse to non-human primate). Herein, we report the clinical-grade radiochemistry filed with exploratory Investigational New Drug (eIND) and first-in-human PET/MRI evaluation of [ 18 F]FTC-146. Procedures [ 18 F]FTC-146 is prepared via a direct [ 18 F] fluoride nucleophilic radiolabeling reaction and formulated in 0.9 % NaCl containing no more than 10 % ethanol through sterile filtration. Quality control (QC) was performed based on USP 823 before doses were released for clinical use. The safety and whole body biodistribution of [ 18 F]FTC-146 were evaluated using a simultaneous PET/MR scanner in two representative healthy human subjects. Results [ 18 F]FTC-146 was synthesized with a radiochemical yield of 3.3 ± 0.7 % and specific radioactivity of 8.3 ± 3.3 Ci/μmol ( n = 10, decay corrected to EOB). Both radiochemical and chemical purities were >95 %; the prepared doses were stable for 4 h at ambient temperature. All QC test results met specified clinical criteria. The in vivo PET/MRI investigations showed that [ 18 F]FTC-146 rapidly crossed the blood brain barrier and accumulated in S1R-rich regions of the brain. There were also radioactivity distributed in the peripheral organs, i.e., the lungs, spleen, pancreas, and thyroid. Furthermore, insignificant uptake of [ 18 F]FTC-146 was observed in cortical bone and muscle. Conclusion A reliable and automated radiosynthesis for providing routine clinical-grade [ 18 F]FTC-146 for human studies was established in a modified GE TRACERlab FX FN . PET/MRI demonstrated the initial tracer biodistribution in humans, and clinical studies investigating different S1R-related diseases are in progress.